Кто такой «музыкант Набоков»? (Из комментария к книге А. Ремизова «Учитель музыки») [Who is “the Musician Nabokov”? Rereading Aleksey Remizov’s _The Music Teacher_] - Dotsenko, Sergei (Slavica Revalensia, 2022)
This article is a close reading of a passage from _The Music Teacher_ by Aleksey Remizov mentioning “the musician Nabokov,” who changes his Paris apartments so often that letters to him fail to reach their addressee. Although the most likely person this passage seems to be hinting at is Nicolas Nabokov, a composer, it should rather be seen as a tongue-in-cheek attack against the composer’s cousin, Vladimir Nabokov — a writer who was at odds with Remizov. Remizov [justkui ütleb, et] person changing apartments too often, does not exist — he is nothing (and this is something Remizov would not have said about Nicolas Nabokov).